Rancang Bangun Aplikasi Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT.Lovely Corpin Tour & Travel Surabaya - Ayu, Hermawati Tika; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal JSIKA, 2013)
Abstract PT. Lovely Corpin Tour & Travel is a company that serving for domestic and international tour including Bali, Manado, Singapore, Bangkok, Thailand, and Malaysia. This company has a problem to analize customer satisfaction level from the strongest until the weakest. It happens because those are so many complaint and questionnaire which filled by customer that haven’t all recapitulated.The problem can be solved by customer statisfaction application to know the level of customer satisfaction from the strongest until the weakest. Customer statisfaction application created by declare the independent and dependent variable. Based on the independent and dependent variable can be found cause and effect so that customer statisfaction application is using multiple linear regression. Next steps are implement and evaluate the application to make sure it run as expected. The result showed that aplication have testing values 100% and fisible. Based on the result of test, aplication using by 65 user, the result service quality factor that effect of customer satisfaction is emphaty factor 58,45%. Keywords: Application Effect Of Analysis Service Quality, Customer Satisfaction, Multiple Linear Regression.